Time-resolved pump-probe spectroscopy to follow valence electronic motion in molecules: application - Dutoi, Anthony; Cederbaum, Lorenz S. (Physical review. A, Atomic, molecular, and optical physics, 2014)
Numerical experiments are performed using a recently published formalism [Phys. Rev. A 88, 013419 (2013)] for computing the transient absorption of an attosecond x-ray probe by a molecule in a nonstationary valence-excited state. This study makes use of an all-electron correlated electronic-structure model to compute electronic dynamics ensuing after a localized excitation on a model chromophore group. Simulated absorption of a delayed attosecond pulse is then used to investigate the presence of an extra valence electron or vacancy around atoms of a given element as a function of time, by tuning the carrier frequency to the associated core-valence energy gap. We show correlations between the predicted absorption of such pulses and visualizations of the particle and hole locations in test molecules. Given the strong role played by the relative orientation of the molecules and the probe polarization, results are presented for a few different alignment schemes. For the molecules studied, effective pump-induced alignment is sufficient to recover easily interpreted information.
Gesehen am 29.07.2020